The Construction and Structure Reliability of Jam Gadang: The Heritage of West Sumatera - Khadavi, Khadavi; Yulcherlina, Yulcherlina (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2018)
The Big Ben (Jam Gadang) is a tower building of 28.295 meters height positioned as the landmark and the heritage of both Bukittinggi city and West Sumatra province. It was built in 1926 by architects Yazin and Sutan Gigi Ameh as the gift from the Queen of the Netherlands to the controleur (secretary of Bukittinggi City). Major perception of the people that Jam Gadang was build by using masonry for the entire building. Following massive earthquakes in 2007 the Indonesian Heritage Trust in cooperation with the Shared Heritage Program of the Netherlands initiate full investigation of the tower. The activity was aimed at gathering data of the structure and analyzes the reliability of the current structure of the building. The result of such activities found that the construction of Jam Gadang consist of reinforced concrete with the compressive strength ≥ 25Mpa on average, the foundation consists of full stone with the prism shape until -1,800 mm. The column have a dimension with variation of 800 mm x 800 mm at the first floor and 400 mm x 400 mm at the top floor of the tower, with 18 mm longitudinal and 10 mm shear reinforcement, the beam and plate have the composite structure of steel beam H 105.90.10.25. The modeling and analysis of the structural reliability of Jam Gadang tower for earthquake load based on the Indonesian Code SNI-03-2847- 2002, with maximum lateral deformation of (δmax) 63.00 mm which is smaller than lateral deformation limit of 83.70 mm.